Tempat Kedudukan Rest Lingual dalam Pembuatan Gigi Tiruan Sebagian Lepas Kerangka Logam Lingual Rest Seat in Removable Partial Denture - Armida Sofyanis (Faculty of Dentistry, Universitas Indonesia, 2015)
In certain cases, lingual rest is needed to provide better retention for RPD. Lingual rest is a cingulum rest placed on the lower jaw in RPD design. It is used as an indirect retainer. To make the rest fit best, a good rest seat should be prepared in the cingulum. The outline form of the lingual rest is a half moon shaped with a smooth curve from one marginal ridge to the other, crossing the center of the tooth. The rest seat itself should be V shaped, and the depth is 1 - 1 1/2mm. In this situation, one of four options should be considered i.e.: fabricate a cast veneer crown, or a three quarter crown to place a lingual pin-lay, or put a small amalgam restoration in the base of the preparation when the dentin has been touched.